Relationship between bird species diversity and tree composition in Coban Talun waterfall area, Batu, East Java - Muhammad Muizzul Ma'ruf; Ariqson Rizqi Mohammad; Nuris Shabrina; Intan Fatimah Az-zahrah; Aini Lutfi Nur Aida (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2026)
Birds and trees are interrelated and can therefore be used as bioindicators of environmental quality. Trees provide food and shelter for various bird species, while birds assist in tree pollination. The relationship between bird species diversity and tree composition in the Coban Talun tourist area has not been specifically studied, therefore this study aims to assess the environmental quality in the Coban Talun tourist area through an analysis of the relationship between bird species diversity and tree composition. The method used to observe tree composition was inventory, while the point count and line transect methods were used to observe birds. The data analysis used was Spearman's rank correlation test to analyze the relationship and influence between plant diversity and the number of bird species and individuals. Based on the analysis results, it was found that station 1 (pine forest) was dominated by the Yellow-crested Bulbul (Pycnonotus aurigaster), which took advantage of the presence of fruit trees, while station 2 (fields) was dominated by the Linchi Swiftlet (Collocalia linchi), which adapted to open areas. Bird diversity increased in areas with higher tree diversity, indicating a positive relationship between vegetation composition and bird abundance. This correlation confirms that tree structure and diversity play an important role in providing habitat, food, and activity space for birds, so that the relationship between these two components can be used as an indicator of environmental quality.